1998
DOI: 10.1002/(sici)1097-4636(19980605)40:3<464::aid-jbm18>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial phenomena: Anin vitro study of the effect of calcium phosphate (Ca-P) ceramic on bone formation

Abstract: In previous studies we developed a RF magnetron sputter technique for the production of thin Ca-P coatings. With this technique coatings can be produced that vary in Ca/P ratio as well as in structural appearance. The aim of this investigation was to obtain more understanding of the biological behavior of these coatings by way of in vitro experiments. The effect of noncoated titanium (Ti) and three different Ca-P-sputtered surfaces on the proliferation and differentiation (morphology and matrix production) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 32 publications
(29 reference statements)
2
32
0
Order By: Relevance
“…25 Furthermore, Hulshoff et al reported that the bone marrow cells formed more mineralized extracellular matrices on magnetron-sputtered Ca-P coating titanium than pure titanium, and the proliferation of the cells was significantly higher on the pure titanium than the coated titanium. 41 Our results are consistent with these data. Apatite formed on titanium probably promotes adsorption of proteins from the serum, which are then subsequently utilized by the osteoblasts to form a mineralized extracellular matrix, as previously described.…”
Section: Discussionsupporting
confidence: 91%
“…25 Furthermore, Hulshoff et al reported that the bone marrow cells formed more mineralized extracellular matrices on magnetron-sputtered Ca-P coating titanium than pure titanium, and the proliferation of the cells was significantly higher on the pure titanium than the coated titanium. 41 Our results are consistent with these data. Apatite formed on titanium probably promotes adsorption of proteins from the serum, which are then subsequently utilized by the osteoblasts to form a mineralized extracellular matrix, as previously described.…”
Section: Discussionsupporting
confidence: 91%
“…With RF magnetron sputter technique coatings can be produced that vary in Ca/P ratio as well as in structural appearance (Hulshoff et al 1998). All heat-treated coatings appeared to be stable in simulated body fluid (Yonggang Yan et al 2006).…”
Section: In Vitro Studymentioning
confidence: 99%
“…The advan tages of this process are that the deposited films are very thin (100 nm -4 pm), well-defined in structure and composition, and strongly bonded to the underlying metal substrate. Previous cell cul ture and animal experiments (Hulshoff et aL 1995(Hulshoff et aL , 1996b already showed the biological feasibility of this type of coating.…”
mentioning
confidence: 99%